Controlling Threshold and Resistive Switch Functionalities in Ag‐Incorporated Organometallic Halide Perovskites for Memristive Crossbar Array. (11th December 2022) - Im, In Hyuk; Kim, Seung Ju; Baek, Ji Hyun; Kwak, Kyung Ju; Lee, Tae Hyung; Yang, Jin Wook; Lee, Da Eun; Kim, Jae Young; Kwon, Hee Ryeong; Heo, Do Yeon; Kim, Soo Young; Jang, Ho Won
Abstract: Halide perovskites (HPs) can be the effective functional materials for the sneak‐path current issue in the memristive crossbar array. Herein, an efficient strategy is proposed to integrate the HPs‐based bidirectional threshold and bipolar resistive switches (TS and RS). The resistance change characteristics from volatile threshold to nonvolatile resistive switching are modulated by controlling Ag doping concentration in the MAPbI3 . HPs provide the diffusive condition and the quantity of Ag regulates the radius of its network. A low amount of Ag contributes to weak network with a short lifetime. However, when the amount of Ag increases, the conductive filament becomes more robust, showing a long lifetime. A MAPbI3 :Ag TS with a low Ag content is developed, showing a steep switching slope (1 mV per decade), fast switching speed (< 80 ns), and low off‐current (10 nA). And, a MAPbI3 :Ag RS with a high Ag content is developed, showing multilevel storage capability and long retention time (1400 s). Finally, these TS and RS coupled into the 1S‐1R integrated component, resulting the development of the maximum crossbar array size to 1.4 × 10 12 . This study offers an efficient methodology for tailoring the resistance change characteristics and a promising strategy for practical HPs‐based memristive crossbar application. Abstract : A low amount of Ag contributes to the network with a short lifetime. When the amount of Ag increases, the conductive filament becomes more robust, showing a long lifetime. A MAPbI3:Ag‐based threshold switch and resistive switch is developed. They are coupled into the 1S‐1R integrated component, resulting the development of the maximum crossbar array size to 1.4 × 10 12 .